Reaction-diffusion model as framework for understanding the role of riboflavin in "eye defence" formulations. Issue 25 (16th April 2020) - Di Nezza, Francesca; Caruso, Ciro; Costagliola, Ciro; Ambrosone, Luigi
Abstract : Analysis of UV-visible spectra, performed on commercial riboflavin-based eye drops, showed that absorbance is a saturating function of vitamin concentration. Abstract : Analysis of UV-visible spectra, performed on commercial riboflavin-based eye drops, showed that absorbance is a saturating function of vitamin concentration. This implies a threshold concentration, C t, such that for riboflavin concentration > C t the absorbance remains constant and the effectiveness of the eye drops is independent of the dose used. These experimental results were combined with a diffusion–reaction model to elucidate the mechanism of action within the cornea. The model predicts that the eye drops have a low effectiveness on UVB and UVC, while they have a good performance for UVA. Indeed, at the center of the cornea the transmittance is significantly reduced and after 1 h it is reduced by about 70% compared to a cornea devoid of eye drops.